Hoinga: A supernova remnant discovered in the SRG/eROSITA All-Sky Survey eRASS1 - Becker, W.; Hurley-Walker, Natasha; Weinberger, C.; Nicastro, L.; Mayer, M.G.F.; Merloni, A.; Sanders, J. (EDP SCIENCES S A, 2021)
Supernova remnants (SNRs) are observable for about (6-15) × 104 yr before they fade into the Galactic interstellar medium. With a Galactic supernova rate of approximately two per century, we can expect to have of the order of 1200 SNRs in our Galaxy. However, only about 300 of them are known to date, with the majority having been discovered in Galactic plane radio surveys. Given that these SNRs represent the brightest tail of the distribution and are mostly located close to the plane, they are not representative of the complete sample. The launch of the Russian-German observatory SRG/eROSITA in July 2019 brought a promising new opportunity to explore the Universe. Here we report findings from the search for new SNRs in the eROSITA all-sky survey data which led to the detection of one of the largest SNRs discovered at wavelengths other than the radio: G249.5+24.5. This source is located at a relatively high Galactic latitude, where SNRs are not usually expected to be found. The remnant, 'Hoinga', has a diameter of about 4. °4 and shows a circular shaped morphology with diffuse X-ray emission filling almost the entire remnant. Spectral analysis of the remnant emission reveals that an APEC spectrum from collisionally ionised diffuse gas and a plane-parallel shock plasma model with non-equilibrium ionisation are both able to provide an adequate description of the data, suggesting a gas temperature of the order of kT = 0.1-0.02+0.02 keV and an absorbing column density of NH = 3.6-0.6+0.7 × 1020 cm-2. Various X-ray point sources are found to be located within the remnant boundary but none seem to be associated with the remnant itself. Subsequent searches for a radio counterpart of the Hoinga remnant identified its radio emission in archival data from the Continuum HI Parkes All-Sky Survey and the 408-MHz 'Haslam' all-sky survey. The radio spectral index α = -0.69 ± 0.08 obtained from these data definitely confirms the SNR nature of Hoinga. We also analysed INTEGRAL SPI data for fingerprints of 44Ti emission, which is an ideal candidate with which to study nucleosynthesis imprinting in young SNRs. Although no 44Ti emission from Hoinga was detected, we were able to set a 3σ upper flux limit of 9.2 × 10-5 ph cm-2 s-1. From its size and X-ray and radio spectral properties we conclude that Hoinga is a middle-aged Vela-like SNR located at a distance of about twice that of the Vela SNR, i.e. at ~500 pc.